Implementation of Transfer of Sentenced Person in the Prespective of National and International Law (Marry Jane Case) - Diajeng Maurien Rachma Ayu Queentania; Sonny Saptoajie Wicaksono (Universitas Negeri Semarang, 2025)
This study discusses the regulation and implementation of Transfer of Sentenced Person (TSP) from the perspective of international and national law. The international legal basis that is still used today is the multilateral agreement Convention on the Transfer of Sentenced Person in 1983 drafted by the Council of Europe. Indonesia uses Law Number 22 of 2022 concerning Corrections and relies on bilateral agreements with other countries based on the principles contained in the Convention on the Transfer of Sentenced Person. The Mary Jane case is one of the cases of prisoner transfers that have been carried out by Indonesia with the Philippines using a practical arrangement. The absence of universal and comprehensive legal regulations governing the transfer of prisoners both in international and national law and the need to regulate TSP encourages the Indonesian government to immediately ratify the Draft Law on the Transfer of Sentenced Person (TSP) Between Countries.